Annealing of selective laser melted NiTi shape memory alloy - Khoo, Zhong Xun (2018)
Coupled with the poor manufacturability of nickel titanium (NiTi) and the limitations of conventional technologies, the majority of the produced NiTi parts have simple geometries. This limits the applicability of NiTi, despite it having exceptional functional properties. Hence, Selective Laser Melting (SLM) has been proposed as an alternative method in fabricating complex NiTi structures. In the prior work, repetitive scanning has been utilised to produce high-quality samples. Nevertheless, its shape recovery response can still be further improved. Therefore, in this paper, rapid annealing was introduced to enhance its shape memory properties. It was observed that annealing at 400 °C for a period of 5 minutes produced samples with higher percentages of shape recovery and transformation strain than the non-annealed samples.